Direct or indirect composite for restoring permanent first molars affected by Molar Incisor Hypomineralisation (MIH): a randomized clinical controlled trial - Abdulrhman Hakmi; Mayssoon Dashash (BDJ Open, 2023)
Abstract Aim This study was undertaken to compare direct composite resin restorations (DCRR) and indirect composite resin restorations (ICRR) for treating permanent first molars affected by MIH in terms of clinical performance. Materials and methods This was a controlled, randomized, clinical split-mouth study. The studied sample consisted of 40 asymptomatic first permanent hypomineralised mandibular molars in 20 children aged between 7–11 years, these cases were divided randomly into two groups: Group 1 (experimental): 20 first permanent mandibular molars were restored with ICRR, and Group 2 (control): 20 first permanent mandibular molars that were restored with DCRR. The cavity was prepared using a diamond bur on a high-speed handpiece, and the prepared cavity was wiped with cotton moistened with sodium hypochlorite. The composite was applied directly with a total-etch bonding system. In the ICRR group, an impression for the prepared cavity was taken using a silicon-based material, and the restoration was adhesive with self-adhesive resin cement. The child’s satisfaction with each of the two application techniques was assessed through the scale FACES. Restorations were evaluated during follow-up periods (3, 6, and 12 months) according to Modified USHPH criteria. Results The clinical success rate was 90% in the ICRR group versus 85% in the DCRR group after 12 months of follow-up without statistically significant differences (P = 0.218). Children were significantly more satisfied (P = 0.0351) with ICRR than DCRR. Conclusions Both DCRR and ICRR can be considered effective restorations with acceptable clinical performance in the restoration of hypomineralised first permanent molars with an advantage of ICRR in terms of child acceptance of the restoration application technique.